2022
DOI: 10.1038/s41467-022-34555-4
|View full text |Cite
|
Sign up to set email alerts
|

DOPAnization of tyrosine in α-synuclein by tyrosine hydroxylase leads to the formation of oligomers

Abstract: Parkinson’s disease is a progressive neurodegenerative disorder characterized by the preferential loss of tyrosine hydroxylase (TH)-expressing dopaminergic neurons in the substantia nigra. Although the abnormal accumulation and aggregation of α-synuclein have been implicated in the pathogenesis of Parkinson’s disease, the underlying mechanisms remain largely elusive. Here, we found that TH converts Tyr136 in α-synuclein into dihydroxyphenylalanine (DOPA; Y136DOPA) through mass spectrometric analysis. Y136DOPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Recently, it has been shown that the activity of tyrosine hydroxylase, an enzyme specifically expressed in catecholamine-containing neurons, can induce the hydroxylation of Tyr 136 in the α-Syn sequence. This DOPAnization promoted the α-Syn oligomerization, which may play a pathogenic role in dopaminergic neurodegeneration [ 109 ]. The Y136-DOPA-Syn signal was detected at the striatonigral axon terminals of aged A53T Tg mice and patients with PD or MSA but not in controls.…”
Section: Alpha-synuclein Oligomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the activity of tyrosine hydroxylase, an enzyme specifically expressed in catecholamine-containing neurons, can induce the hydroxylation of Tyr 136 in the α-Syn sequence. This DOPAnization promoted the α-Syn oligomerization, which may play a pathogenic role in dopaminergic neurodegeneration [ 109 ]. The Y136-DOPA-Syn signal was detected at the striatonigral axon terminals of aged A53T Tg mice and patients with PD or MSA but not in controls.…”
Section: Alpha-synuclein Oligomersmentioning
confidence: 99%
“…The Y136-DOPA-Syn signal was detected at the striatonigral axon terminals of aged A53T Tg mice and patients with PD or MSA but not in controls. This suggests that DOPAnization of α-Syn may occur during the disease progression rather than initiating the pathological process, but in any case, it might contribute to the selective loss of dopaminergic neurons in synucleinopathies [ 109 ].…”
Section: Alpha-synuclein Oligomersmentioning
confidence: 99%
“…As for tyrosine oxidation in regard to ɑ-syn and PD, it is also relevant that the oxidation of free tyrosine produces L-DOPA. Indeed, DOPAnization of tyrosine in α-syn by tyrosine hydroxylase (TH) leads to the formation of oligomers (Jin et al 2022 ). L-DOPA has pro-oxidant properties and can modify ɑ-syn (Post et al 2018 ) and so increase the sensitivity to oxidative stress and degeneration of catecholaminergic neurons (Lipski et al 2011 ).…”
Section: A Closer Look At ɑ-Synuclein and Lbsmentioning
confidence: 99%
“…Calpain over-activation is observed in various neurological disorders and injuries such as PD, AD, muscular dystrophy, traumatic brain injury, and spinal cord injury. Its activity increases with mutated α-syn [115]. Activation of the RhoA pathway plays a crucial role in cell signaling in both neurons and glial cells [116][117][118].…”
Section: Calpain's Role In Neuroinflammation and Pdmentioning
confidence: 99%